Ius Constituendum Dalam Sinkronisasi Kewenangan Penyelesaian Sengketa Jurnalistik di Bidang Penyiaran (Kajian Revisi Undang-Undang Penyiaran) - Melki T. Tunggati (LPPM Universitas Bina Taruna Gorontalo, 2024)
The authority to resolve journalistic disputes in broadcasting has become a polemic after the revised draft of broadcasting law was presented in the Legislation Body Meeting on March 27, 2024. The draft revision of broadcasting law gives authority to the Indonesian Broadcasting Commission in resolving journalistic disputes in broadcasting, which is currently owned by the Press Council. Any indication of dualism in authority will certainly have implications for legal uncertainty. Institutionally, there will also be potential for sectoral ego because each institution feels it has the capacity to resolve disputes. This research uses normative research that uses legal and conceptual approaches as the basis of analysis. The result of this research shows that journalistic dispute settlement mechanism in broadcasting is not regulated in Press Law or Broadcasting Law, but journalistic dispute settlement in broadcasting is the authority of Press Council. The weakness of journalistic dispute settlement authority in broadcasting as stipulated in the Draft Revision of Broadcasting Law is that it takes over the authority of the Press Council and there is a paradox in the formation of regulations. Establishing institutional self-regulation and building good intercorrelation and chemistry related to the synchronization of the authority to resolve journalistic disputes in the field of broadcasting is the goal in the ius constituendum.